Struggle Against Male Domination In Harem Tradition As Reflected In Fatima Mernissi's Dreams Of Trespass: Tales Of A Harem Girlhood - Wardani, Kusuma; , Prof. Dr. C. Bakdi Sumanto; , Dr. M. Thoyibi, M.S (2014)
The objectives of the research are (1) to reveal Fatima Mernissi's struggle against male domination, and (2) to reveal Fatima Mernissi's criticism against women marginalization. The research method is descriptive qualitative method. The data source are taken from the text in Dreams of Trespass: Tales of A Harem Girlhood that cover words, phrases, clauses sentences, dialogues, narrations and also textbooks, internet, journals or articles. The technique of data analysis uses taking note, paraphrase, reading from the data source to find out the theory and information. Radical Feminist Theory and Postcolonial Theory are used to scrutinize Moroccans' ideology. The finding of the research is the root of women's oppression is patriarchy. In Dreams of Trespass: Tales of A Harem Girlhood, Mernissi shows that patriarchy becomes the foundation to oppress women through the inequality treatment between female and male infant in her harem and Moroccan's society where the sex differences become the huge matter since they were born, in household task, economic, information, education, politics, women hair business, beauty norms and traveling. This study also discovers that violence against women is related with the subordinate of women status in society. It occurs through gender based violence which is including physical, sexual, psychological, and economic abuse. Patriarchy makes a supreme effort to use their domination based on the falsely interpretation of religious tenets, tradition through the cultural practice, norm in the family council to refuse all the matters which probably endanger the existence of patriarchy such as women's limited access to the justice system in the equal divorce rights and early marriage where the doers are men who live with the same house with them as husband, father, cousin, nephew and sibling in the family. It is almost impossible disclosed when it occurs in a private place and particularly if male family members are responsible for the violations. Women as the victims are reluctant to defend their rights in the name of family reputation. The finding further discovers that women become the important variable in subaltern class. There is no subject position for women to speak up, express their idea and represent themselves. Subaltern women are addressed to Mernissi's women who are totally in silence to right for education, Illiteracy, dress code and fashion, mealtime, movies, hammam (public bath), picnic and hadra. As the oppressed subject, they need awareness to speak and only the educated people who can help them to speak up and also give them proper education and prosperity.